2013
DOI: 10.3324/haematol.2012.081885
|View full text |Cite
|
Sign up to set email alerts
|

Actual prognosis during follow-up of survivors of B-cell non-Hodgkin lymphoma in the Netherlands

Abstract: © F e r r a t a S t o r t i F o u n d a t i o nstage, 16 were obtained routinely from the medical records about 9 months after diagnosis.In addition to passive follow-up via the hospitals, date of death was also retrieved from the Municipal Personal Records Database. Follow-up of vital status was complete until January, 1 st , 2010. For the present study, all patients with mature B-cell NHL newly diagnosed in the period [1989][1990][1991][1992][1993][1994][1995][1996][1997][1998][1999][2000][2001][2002][2003][… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 36 publications
1
7
4
Order By: Relevance
“…Prior studies of conditional RS patterns in lymphoma patients have noted that in patients with indolent lymphomas such as CLL/SLL, RS5 is more or less unchanged after stratifying on time-since-diagnosis [22]. In contrast, the current study demonstrated that duration of treatment-free survival since diagnosis was predictive of modest but steady improvements in RS5.…”
Section: Discussioncontrasting
confidence: 62%
“…Prior studies of conditional RS patterns in lymphoma patients have noted that in patients with indolent lymphomas such as CLL/SLL, RS5 is more or less unchanged after stratifying on time-since-diagnosis [22]. In contrast, the current study demonstrated that duration of treatment-free survival since diagnosis was predictive of modest but steady improvements in RS5.…”
Section: Discussioncontrasting
confidence: 62%
“…The present study thus extends on these series by predicting survival for patients diagnosed during 2015–2019. Five-year RS estimated at diagnosis was higher in our study (85; 95% CI, 84–87%), as compared to the earlier series in the Netherlands (72; 95% CI, 71–73%) 3 and the U.S. study (82; 95% CI, 81–83%) 4 . Akin to previous studies in FL, we observed a slight increase in CRS during follow-up that was less pronounced as compared to other types of lymphomas 3 , 4 , 9 , 10 .…”
contrasting
confidence: 77%
“…Therefore, survival estimates for patients who have survived from a specified time since diagnosis—especially when corrected for the life expectancy in the general population—add relevant information related to changing survival expectations over time (i.e., conditional relative survival; CRS). At present, published data on CRS in FL are sparse and reasonably outdated 3 , 4 . For this reason, in this nationwide, population-based study, we predicted up-to-date estimates of 5-year relative survival (RS) at diagnosis, and for each additional year survived up to 10 years post-diagnosis among contemporary diagnosed FL patients in the Netherlands using techniques that are conceptually similar to those that estimate the life expectancy at birth.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Conditional relative survival data from the NCR has been described previously for colorectal 26 and prostate 27 cancer as well as for non-Hodgkin lymphoma. 28 For survivors of endometrial and ovarian cancer in the current study sample who were included within 1 year after diagnosis, the 5-year survival at the time of diagnosis by cancer stage was determined (www. cijfersoverkanker.nl).…”
Section: Methodsmentioning
confidence: 99%